Mortaria from Križanke in the eastern suburb of Emona - Mitrova, Danica; Vinazza, Manca (Arheološki vestnik, 2025)
The article focuses on Roman ceramic mortaria discovered during the 2018 archaeological excavations in the Križanke complex in Ljubljana. This area’s continuous use from the Middle or Late Augustan period until the decline of Emona is reflected in the wide chronological range of these vessels. The study applies the chaîne opératoire approach by analysing the macroscopic and microscopic paste composition, the forming and shaping techniques, the typology, and the chronological framework. Eight technological groups were identified, distinguished primarily by the presence or absence of a glaze. The unglazed mortaria come from two production zones: Central-Southern Italy and Northern Italy. Two potters’ stamps confirm the Po Valley as the area of origin, with the locations of their workshops being more narrowly defined through mineralogical-petrographic analysis. The glazed mortaria most likely originated elsewhere, but their exact provenance remains uncertain.